Biology of a deep-water sea anemone (Anthozoa: Actiniidae) from eastern Canada: Spawning, development, and growth. (March 2017) - Mercier, Annie; Baillon, Sandrine; Daly, Marymegan; Macrander, Jason; Hamel, Jean-François
Abstract: Knowledge of the general biology and reproductive ecology of deep-water species can help predict their resilience to environmental and anthropogenic disturbances. The present study centers on live specimens of a deep-water sea anemone which were collected at bathyal depths between 1100 and 1400 m and kept in a mesocosm for over 6 years. Morphology and DNA sequencing confirmed that the species belongs to the genus Urticina . Male and female (9–10 cm pedal disk diameter, 90 tentacles) spawned 4 years post collection, in early spring (March). Both sexes released gametes through the mouth. The negatively buoyant oocytes (550–600 µm in diameter) quickly settled on the rocks and soft sediments surrounding the female. Lecithotrophic embryonic and larval development occurred on the substratum. Fully developed planula larvae were detected after 17–21 days. Planulae started to crawl and swim around but remained demersal. Metamorphosis and settlement occurred after 30–35 days, exclusively on hard substrata and preferentially on undersurfaces. Offspring grew slowly, developing 8 tentacles after 5 months and 24 tentacles after 12 months (3–4 mm pedal disk diameter). After 2.6 years of growth, the captive-born sea anemones reached 12–16 mm in pedal disk diameter and possessed 48–54 tentacles.